ナンキョク ミナミ ビクトリアランド ノ ラビリンス ニ オケル チスイ チュウ ノ ゼン ユウキ タンソ - 松本, 源喜; マツモト, ゲンキ; 綿抜, 邦彦; ワタヌキ, クニヒコ; 鳥居, 鉄也; トリイ, テツヤ; Matsumoto, Genki I.; Watanuki, Kunihiko; Torii, Tetsuya (1987)
P(論文) 南極南ビクトリアランド・ライト谷上部のラビリンス(77°33′S, 165°50′E)に分布する, 10個の池の全有機炭素(TOC)を測定した。TOC値は池水間で大きく異なる(0.78-23mgC/l)が, 高濃度のTOCは塩池水のみで測定された。電気伝導度とTOC値間には, かなり高い正の相関(0.82)がみられた。このことは次のように解釈される。1)まず降雪や氷河融水に含まれていた有機物が, 池水の凍結により残液に濃縮される。2)次いで池内の生物生産による有機物が加わるとともに, 容易に微生物分解を受ける有機物が除去される。3)さらに池水の蒸発と凍結が繰り返されることにより, 長年月の間に比較的分解しにくい有機物が, 溶存無機塩類とともに池底付近に蓄積される。 Total organic carbon (TOC) in 10 freshwater and saline ponds in the Labyrinth (77°33′S, 160°50′E) of southern Victoria Land, Antarctica, was preliminary studied to clarify their distribution and sources. The TOC concentrations ranged from 0.78 to 23.1mgC/l. The high TOC concentrations were found only in saline pond waters. The correlation coefficient between electric conductivity and TOC value was considerably high (0.82). This result can be explained as follows : Organic substances supplied from snow and glacial meltwaters are first concentrated in the residual pond waters by freezing out. Also in situ photosynthetic activity produces organic substances, but certain labile organic constituents may be degraded by microbial activity. Further, repeating freezing and evaporation of pond waters work to concentrate relatively refractory organic substances in the pond bottom waters, together with dissolved inorganic salts over a long period of time. departmental bulletin paper